2009
DOI: 10.1128/jvi.02564-08
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Mediated Suppression of Human T-Cell Leukemia Virus Type 1 Expression In Vitro and In Vivo by Type I Interferon

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) causes adult T-cell leukemia (ATL),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 36 publications
(36 reference statements)
5
56
2
Order By: Relevance
“…Surprisingly, neither treatment of immature DCs with recombinant IFN-α nor culture with supernatant from mature DCs (that contains high amounts of physiological type I IFNs) was able to restrict HTLV-1 infection. This is in contrast with previous studies [19,20] and suggests that therapeutic failure of type I IFN therapy used in some ATL chemotherapy protocols [21] could be due to resistance of DCs to IFN-α treatment. This hypothesis would need confirmation through clinical trials monitoring the proviral load in DCs from ATL patients throughout anti-viral therapy.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Surprisingly, neither treatment of immature DCs with recombinant IFN-α nor culture with supernatant from mature DCs (that contains high amounts of physiological type I IFNs) was able to restrict HTLV-1 infection. This is in contrast with previous studies [19,20] and suggests that therapeutic failure of type I IFN therapy used in some ATL chemotherapy protocols [21] could be due to resistance of DCs to IFN-α treatment. This hypothesis would need confirmation through clinical trials monitoring the proviral load in DCs from ATL patients throughout anti-viral therapy.…”
contrasting
confidence: 54%
“…This led to the observation that the strength of HTLV-1 restriction correlates the level of DC maturation. Because mature DCs produce high amounts of IFN-α and because it is well established that IFN-α has anti-HTLV-1 activity in other cell types [19,20], we then asked whether HTLV-1 restriction in mature DCs was due to the antiviral effect of IFN-α. Surprisingly, neither treatment of immature DCs with recombinant IFN-α nor culture with supernatant from mature DCs (that contains high amounts of physiological type I IFNs) was able to restrict HTLV-1 infection.…”
mentioning
confidence: 99%
“…It was shown that HTLV-1 gag mRNA decreased when HTLV-1-immortalized (interleukin 2 [IL-2]-dependent) T cells were cocultured with human 293T or murine NIH 3T3 nonlymphoid stromal cells (30). This effect was abolished when a poly-clonal neutralizing antibody against IFN-␤ (but not against IFN-␣) was added, indicating that IFN-␤ produced by stromal cells could inhibit virus production.…”
mentioning
confidence: 93%
“…HUT102 cell line, which has the capacity for IL-2-independent cell growth, was also used (1). ILT-Hod and HUT102 were kind gifts from Dr. Mari Kannagi (Tokyo Medical and Dental University, Tokyo, Japan) and Dr. Masahiro Fujii (Niigata University Graduate School of Medical and Dental Sciences, Niigata, Japan) in 2008, who published the manuscripts using these cell lines (18,19). Cell identities were not authenticated by the authors other than confirming the cell lines are ATL cells by Southern blot analysis for viral gene integration and status of Tax expression in addition to characteristic T-cell phenotypic markers.…”
Section: Cellsmentioning
confidence: 99%